Distance from cohesive end site cos determines the replication requirement for recombination in phage lambda. - Stahl, F W (1982)
Previous work showed that crossing-over in the middle of the chromosome of phage lambda requires more DNA replication than does crossing-over near the termini. Relocation of cos, the sequence that determines the lambda termini, alters the requirements for replication in a given marked interval, demonstrating that distance from cos determines the amount of DNA replication that is required for genetic exchange. This result supports a break and copy mechanism for recombination mediated by the red system of phage lambda.